Fiscal Multipliers and Informality - Colombo, Emilio (IMF Working Papers; Working Paper ;, 2022)
This paper investigates the role of informality in affecting the magnitude of the fiscal multiplier in a panel of 141 countries, using the local projections method. We find a strong negative relationship between the degree of informality and the size of the fiscal multiplier. This result holds irrespective of the levels of economic development and institutional quality and is robust to additional country characteristics such as trade, financial openness and exchange rate regime. In a two-sector new- Keynesian model, we rationalize this result by showing that fiscal shocks raise the relative price of official goods, shifting demand towards the informal sector. This reallocation effect increases with the level of informality, because a larger informal sector is associated with a stronger appreciation of relative prices in response to fiscal shocks. Thus, informality raises the size of the unofficial multiplier. A higher degree of non-separability between public and private goods also contributes to rationalize the lower multipliers in high-informality countries.